Implementasi Media Aplikasi Learns Al-Quran With Marbel dalam Meningkatkan Pengembangan Kognitif Anak - Epita Dewi Purnama Fajrin; Amirudin Amirudin; Iqbal Amar Muzaki (FONDATIA, 2022)
In this era of all-digitalization, there are so many advances in technology in various aspects of life, it cannot be denied that studying the Koran is very important especially for children at an early age so that they learn from childhood, of course exciting learning requires learning methods and media Learning the Qur'an by using the Learns Al-Quran with Marbel application will be able to improve cognitive development in children. Therefore, development is a way of working changes that occur in a gradual process through time to time, from a very easy reliability to becoming something difficult that is psychological. Development occurs because it starts from an early age until later in adulthood. Cognitive development is something that is very important to be learned and implemented by children because this cognitive development is a way for progress in children's thinking so that they can develop and working Optimally, with this application media, it will certainly help children in recognizing hijaiyah letters and learning the al-quran . The ongoing activities can certainly stimulate the cognitive aspects of children in learning the Koran which is fun. Cognitive in children is certainly the responsibility of all of us so that the generation of the Indonesian nation more advanced and intelligent, this study uses a qualitative descriptive method because in accordance with existing research, data collection and research was carried out on July 25, 2022, data analysis will be measured by the results of observations of children's cognitive development through the application media learns al-qur'an with marbel significant effect on the cognitive potential of children in learning the al-quran